Melatonin Supplementation in Patients with Complete Tetraplegia and Poor Sleep. (12th March 2013) - Spong, Jo; Kennedy, Gerard A.; Brown, Douglas J.; Armstrong, Stuart M.; Berlowitz, David J.
Abstract : People with complete tetraplegia have interrupted melatonin production and commonly report poor sleep. Whether the two are related is unclear. This pilot study investigated whether nightly supplementation of 3 mg melatonin would improve objective and subjective sleep in tetraplegia. Five participants with motor and sensory complete tetraplegia ingested 3 mg melatonin (capsule) two hours prior to usual sleep time for two weeks. Full portable sleep studies were conducted in participants' homes on the night before commencing melatonin supplementation (baseline) and on the last night of the supplementation period. Endogenous melatonin levels were determined by assaying saliva samples collected the night of (just prior to sleep) and morning after (upon awakening) each sleep study. Prior to each sleep study measures of state sleepiness and sleep behaviour were collected. The results showed that 3 mg of melatonin increased salivary melatonin from near zero levels at baseline in all but one participant. A delay in time to Rapid Eye Movement sleep, and an increase in stage 2 sleep were observed along with improved subjective sleep experience with a reduction in time to fall asleep, improved quality of sleep and fewer awakenings during the night reported. Daytime sleepiness increased however. A randomised, placebo controlled trial with a larger sample is required to further explore and confirm these findings.